Helicobacter pylori Pathogenicity Factors Related to Gastric Cancer - Kianoosh Dadashzadeh; Maikel P. Peppelenbosch; Akyala Ishaku Adamu (Canadian Journal of Gastroenterology and Hepatology)
Background. Although the causal relationship between Helicobacter pylori infection and the development of gastric cancer is firmly established, the exact nature of the pathogenicity factors of H. pylori that predispose to gastric oncogenesis remains incompletely characterized. We investigated the association between H. pylori virulence genotypes and disease in a well-characterized cohort consisting of 109 H. pylori isolates from gastric biopsies originating from patients. Methods. The prevalence of genotype was assessed by PCR and related to clinical histopathological parameters. Results. The relation of babA2 and babB negative and iceA1 positive genotype as a single genotype and the development of cases to GC was statistically significant (P<0.001). The cagE, cagA, and iceA1 were found more commonly in patients with GC as compared with the other groups. The relation of the presence of iceA1 and the development of cases to GC was statistically significant (P=0.008), but babA2 and babB alleles were not detected in these patients. These apparent negative associations were still statically significant (P=0  and 0.005). Conclusion. Our results show an elevated prevalence of infection with H. pylori strains carrying known virulence genotypes with high genetic diversity. This highlights the importance of identifying gene variants for an early detection of virulent genotypes.